A new approach to control the delamination and thrust force during drilling of polymer nanocomposites reinforced by graphene oxide/carbon fiber. (1st December 2020) - Kumar, Jogendra; Kumar Verma, Rajesh; Debnath, Kishore
Abstract: This study proposes a new technique for the diminution of delamination and thrust force generated during drilling of polymer nanocomposites reinforced by Graphene oxide/carbon fiber. These nanocomposites are extensively used in the manufacturing industries, but their machining behavior is remarkably different from conventional metal and their mixtures. In this article, the Box Behnken design with a Simulation annealing algorithm was used for the development of the regression model and simultaneous optimization. The effect of machine parameters, namely, weight % of Graphene oxide (GO), spindle speeds, and feed rate, has been investigated for the quality of the drilled samples. The outcomes was validated through a confirmatory test that reveals a satisfactory agreement with actual ones. The findings reveal that the feed rate is the most prominent factor affecting delamination and thrust trailed by GO wt%. Also, a little error has detected in the predicted results, which confirms the application potential of the proposed module.